War horses of WWI [videorecording (DVD)] - Maddocks, Nick; Pagliero, George; Boulter, Russell (Testimony Films ; Distributed by BFS Entertainment & Multimedia, 2012)
The extraordinary and deeply moving true story of the million British horses who served in World War I. It is told using rare archival materials and testimony, combined with the latest historical research. The story begins with the mass call-up of horses from every farm in Britain and follows their journey through the war. When the war ended, only 60,000 horses made it back to Britain and the most famous war horse to return in glory was Warrior. His story, like the million other British horses who served, should never be forgotten.